STRENGTHENING COLD CHAIN MANAGEMENT IN THE TUNA LOIN INDUSTRY IN BALI: EFFORTS TO IMPROVE PRODUCT QUALITY AND COMPETITIVENESS - Nugraha, I Made Aditya; Khairunnisa, Anis; Cesrany, Mahaldika (Jurnal Penelitian Perikanan Indonesia, 2026)
This study discusses the importance of implementing a cold chain system and optimizing cold storage to support the tuna loin processing process at PT. XYZ. The quality of fishery products, especially tuna, is greatly influenced by temperature stability during the post-harvest process to distribution. Uncontrolled temperature fluctuations can cause quality degradation, accelerate damage, and reduce the selling value of the product. The purpose of this study was to evaluate the effect of implementing a cold chain on the quality of tuna loin and its implications for competitiveness in the local and export markets. The methods used include temperature monitoring at each stage of the supply chain, organoleptic and microbiological quality testing, and comparative analysis of product competitiveness with and without a cold chain system. The results showed that consistent temperature control was able to maintain the freshness, texture, and safety of the product, as well as extend its shelf life. The implementation of an optimal cold chain system also contributes to increasing the economic value of the product and the company's ability to meet international export standards. Although technical challenges such as temperature fluctuations during distribution are still found, PT. XYZ shows a commitment to improving temperature monitoring infrastructure and technology. In conclusion, optimizing the cold chain and cold storage system is a key strategy in maintaining product quality, strengthening competitiveness, and improving the sustainability of the fish processing industry, especially in facing the demands of an increasingly competitive global market.